SURGICAL TREATMENT TACTICS FOR OBSTRUCTION. - Kodirova Ziyodakhon Avazbek qizi; Akramova Nozima Akramovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Testicular torsion is an emergency condition that requires urgent diagnosis and surgical intervention to prevent ischemia and necrosis of the organ. The paper systematizes modern data on surgical methods of treating this condition, analyzes their effectiveness and safety. A review of domestic and foreign publications, including materials from the scientific databases Google Scholar, Scopus and PubMed, was carried out. Particular attention is paid to the factors affecting the prognosis, as well as methods of preventing relapses. It has been revealed that the key factor in successful treatment is timely surgical intervention performed within the first 6 hours from the onset of symptoms. The findings highlight the importance of educating healthcare staff and patients about the need to seek care early.